2005
DOI: 10.1038/sj.bmt.1705109
|View full text |Cite
|
Sign up to set email alerts
|

Do minitransplants have minicosts? A cost comparison between myeloablative and nonmyeloablative allogeneic stem cell transplant in patients with acute myeloid leukemia

Abstract: Summary:Allogeneic hematopoietic stem cell transplantation (SCT) is a widely used, cost-intensive procedure. Although pretransplant nonmyeloablative (NMA) or reduced-intensity conditioning regimens appear very promising, prospective studies comparing this approach with the conventional myeloablative (MA) approach in specific hematologic diseases are necessary, especially in patients in whom the conventional approach is not contraindicated. Cost may be an important factor in the decision-making process. We comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 28 publications
3
38
2
Order By: Relevance
“…There was no difference in the 1-year cost in Cordonnier's study, 34 whereas Saito et al 36 reported lower costs for patients receiving RIC than those given MAC: € 80,499 versus € 128,254, respectively. In our study, we also found a cost increase of approximately € 30,000 for patients receiving MAC.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 63%
See 1 more Smart Citation
“…There was no difference in the 1-year cost in Cordonnier's study, 34 whereas Saito et al 36 reported lower costs for patients receiving RIC than those given MAC: € 80,499 versus € 128,254, respectively. In our study, we also found a cost increase of approximately € 30,000 for patients receiving MAC.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 63%
“…More recent studies have estimated the 1-year cost of related and unrelated donor HSCT using bone marrow or peripheral blood stem cells as € 139,414 in Sweden 32 and € 128,800 in the USA. 33 Cordonnier et al 34 reported the total cost of HLA identical sibling HSCT after RIC and MAC in France. The cost for 1 year after HSCT was around € 60,000.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
“…41 On the other hand, engraftment failure rates may be higher and tempo to develop an antileukemic effect may be slower, the latter a potentially catastrophic situation if the transplant is not undertaken when the patient's disease is in complete remission. The graft-versusleukemia effect may be disease-specific, for example, stronger in chronic myeloid leukemia and multiple myeloma when compared to AML and acute lymphoblastic leukemia.…”
Section: Reduced-intensity Conditioning Results For Aml Patientsmentioning
confidence: 99%
“…Cordonnier et al 41 evaluated the financial costs in a small series for myeloablative versus nonmyeloablative transplants in AML patients ( Table 7). The initial hospitalization (mean days) was longer in the myeloablative group, but the nonmyeloablative group had more mean readmission days.…”
Section: Financial Cost Comparisonsmentioning
confidence: 99%
“…Our findings contrast with a small study of 23 patients, where rates of relapse, complications and OS differed, but no difference in costs between the two groups was observed. 38 Several limitations of our study should be explained. First, this is a single-institution observational study with a median follow-up of 3 years for survivors.…”
Section: Discussionmentioning
confidence: 99%